MENIMBANG WAJAH MASKULIN AL-QURAN (KRITIK GENDER DALAM TAFSIR AL-QURAN) - Luqman Abdul Jabbar (Khatulistiwa, 2011)
There is no guarantee that the Qur’an can fully describe God’s ideas and thoughts. Even though God is all-knowing, He cannot transform all his ideas and thoughts to humans. However, this does not indicate the weakness of God, rather it is the limitation of language which serves as the medium of transformation; God’s language is limitless. So, how is it possible for the limited to accommodate the limitless? The Qur’an bounded to Arabic sentence structure, paragraphs, punctuations, vocabulary, including reduction, distortion and development by the language structure itself as well as cultural structure and readers’ subjectivity. So is in the case of gender, the existence of masculinity in the Qur’an also results from the influence of the language structure and the local culture.